Etawa Goat Estrus Quality with Estrus Synchronization - Jihan Pangestuningrum; Sri Pantja Madyawati; Hana Eliyani; Ratna Damayanti; Siti Eliana Rochmi (Universitas Airlangga, 2021)
Background: Estrus synchronization is a way to get a herd of cattle estrus at the same time. This method can increase the reproductive success of livestock, thereby increasing production and population. Purpose: To determine the estrus quality from estrus synchronized Boerja goats, in Trawas District, Mojokerto Regency. Method: Estrus synchronization using an intra-vaginal sponge contains hormone progesterone, combined with the injection of the hormone GnRH. an intra-vaginal progesterone sponge was inserted for 14 days. After 14 days, the goats were injected with the GnRH hormone, then placed in a cage with the male and observed for estrus quality. Result: the average onset of estrus was 40.6 hours, the average color of the goat's vulvar mucosa when estrus was 2.3 (dark pink), the average presence of mucus was 1.9 (excess vulvar mucus), the average mucus color is 2.8 (white), and the average temperature increase of the vulva when the goat is in estrus is 0.4 ° C. Conclusion: The observations showed that the estrus quality of the goats was very diverse and not all goats were able to show the maximum estrus quality. It can be due to genetic factors, body condition, and feed nutrition.